Neutrophil-Lymphocyte Ratio as a Novel Biomarker for Diabetic Nephropathy in Type 2 Diabetes Mellitus Patients: A Cross-Sectional Study - Pradesta, Rahnowi; Novadian; Yulianto Kusnadi; Nova Kurniati; Syarif Husin (HM Publisher, 2025)
Background: Early detection of diabetic nephropathy (DN) is crucial to prevent progression to end-stage renal disease. The gold standard for diagnosing DN involves urine microalbumin testing and renal biopsy. However, the availability of these diagnostic tools is limited in many healthcare facilities across Indonesia. Consequently, there is a pressing need for an alternative examination that is readily accessible and can effectively monitor the progression of DN. Methods: This cross-sectional study was conducted at Dr. Mohammad Hoesin General Hospital, Palembang, from February 2024 to May 2024. The study aimed to investigate the correlation between neutrophil-lymphocyte ratio (NLR) and urinary albumin levels in type 2 diabetes mellitus (DM) patients. NLR, calculated from complete blood counts, has emerged as a potential inflammatory marker for various conditions. A total of 65 participants diagnosed with type 2 DM were enrolled in the study. Data analysis involved Spearman's correlation test to assess the relationship between NLR and urinary albumin levels. Results: The majority of the 65 subjects were female (58.5%). The study found that 44 subjects had normoalbuminuria, 18 had microalbuminuria, and 3 had macroalbuminuria. A significant positive correlation was observed between NLR and albuminuria levels in type 2 DM patients (r = 0.795; p < 0.01). Conclusion: The study's findings suggest that NLR is a potential cost-effective biomarker for the early detection of DN in type 2 DM patients, especially in resource-limited settings. Further large-scale studies are recommended to validate these findings and establish specific NLR thresholds for predicting DN progression.